2015
DOI: 10.1371/journal.pone.0138017
|View full text |Cite
|
Sign up to set email alerts
|

Readability and Content Assessment of Informed Consent Forms for Medical Procedures in Croatia

Abstract: BackgroundHigh quality of informed consent form is essential for adequate information transfer between physicians and patients. Current status of medical procedure consent forms in clinical practice in Croatia specifically in terms of the readability and the content is unknown. The aim of this study was to assess the readability and the content of informed consent forms for diagnostic and therapeutic procedures used with patients in Croatia.Methods52 informed consent forms from six Croatian hospitals on the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 20 publications
1
27
0
6
Order By: Relevance
“…The education level of Chinese resident was relatively low, with 37.46% at or below the primary school level and 36.18% at the secondary school level [ 23 ], leading to the reading difficulties for the participants. Similarly, other studies found that ICFs from the United States, New Zealand, France, Spain, and Croatia failed to offer subjects complete information using clear and direct language [ 11 , 16 18 , 28 , 29 ]. 97% of Canadian ICFs used appropriate section headings to label the separate sections of content, and such headings were helpful for reading comprehension, and the results are just consistent with ours [ 16 ].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The education level of Chinese resident was relatively low, with 37.46% at or below the primary school level and 36.18% at the secondary school level [ 23 ], leading to the reading difficulties for the participants. Similarly, other studies found that ICFs from the United States, New Zealand, France, Spain, and Croatia failed to offer subjects complete information using clear and direct language [ 11 , 16 18 , 28 , 29 ]. 97% of Canadian ICFs used appropriate section headings to label the separate sections of content, and such headings were helpful for reading comprehension, and the results are just consistent with ours [ 16 ].…”
Section: Discussionmentioning
confidence: 87%
“…Also, ICFs should be written in simple, easy-to-read language to ensure that participants can fully understand all the information in ICFs [ 10 ]. However, as a matter of fact, some researchers have not fully accounted for the age, education level and mental ability of subjects or their representatives [ 11 ], which may increase the likelihood of regretting their participation or withdrawing from the study [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TE se bavi načelom jednakosti pri dodjeli organa, što uključuje nepoželjnu diskriminaciju s obzirom na dob primatelja. 16 17,18 Moguće je, stoga, da pacijent ipak nije dobro percipirao potrebne informacije i da je to utjecalo na ovakav izbor, odnosno odbijanje TX-a. Kako god, načelo poštovanja autonomije bolesnika u odlučivanju o svojemu liječenju u ovom slučaju nije sporno, ali stvara situaciju neuobičajenu i različitu od onih kojima se bave izvješća iz drugih sredina.…”
Section: Uvodunclassified
“…Consent forms in the usa are typically written at a 15 th -grade reading level (typically achieved by the third year of college), even though the average reading level in american adults is only about 8 th grade and medical authorities typically recommend that the readability level of materials for patients should not exceed 6 th grade [18]. Despite the fact that consent forms are essential for the proper transfer of information between medical staff and patients, their readability is often unsatisfactory; such forms also predominantly focus on the risks and benefits of the given medical treatment and fail to properly cover the risks and benefits of alternative treatments and of no treatment [19]. a patient's consent to receive medical treatment also widely functions as evidence of the patient's expressed will, especially in legal and formal proceedings: the widely accepted and commonly used verbal consent is of very doubtful value in this context when expressed without the presence of witnesses and not confirmed in written form; medical staff members are increasingly aware of this problem [20].…”
Section: Basic Practical Obstacles Associated With Patients' Consent mentioning
confidence: 99%